Prospects For the Development of The Digital Economy in The Republic of Uzbekistan - Asraev Umar Muminovich (Euro Asian Journal Publishing, 2024)
The issues of transformation of the development of information and communication technologies and its impact on economic growth in the context of digitalization are considered
Keywords: ICT; digital economy; Internet; competitiveness